Comparative Study of the Cleanliness of Interstitial‐Free Steel with Low and High Phosphorus Contents. Issue 5 (25th January 2021) - Li, Yihong; He, Yibo; Ren, Zhifeng; Bao, Yanping; Wang, Rui
Abstract : Herein, a study comparatively investigating the total oxygen (TO) and nitrogen (N) contents, evolution of inclusions, variations in slag composition, and nozzle clogging during the production of an interstitial‐free (IF) steel and a P‐containing high‐strength (HS) IF steel is presented. The results show that during the production of both steels, the TO content gradually decreases after the deoxidation, with the TO content in the molten steel in the tundish below 30 ppm. There is no significant variance in the N content. The two steels have similar quantities of small inclusions of similar types and sizes. However, the P‐containing HS IF steel has a much higher content of large inclusions, which mainly come from the entrapped mold powder and peeled‐off nozzle clogging. Compared to the common IF steel, the P‐containing HS IF steel has a higher MnO content in the slag during the Ruhrstahl–Heraeus process, compromising cleanliness control; the P‐containing HS IF steel has more significant mold liquid‐level fluctuations and more nozzle clogging, which mainly consists of Al2 O3 and TiO2 . The cause of these issues during the production of the P‐containing HS IF steel is concluded to be related to the high P content. Abstract : Compared to common interstitial‐free (IF) steel, P‐containing high‐ strength IF steel is more susceptible to liquid‐level fluctuations in the mold and nozzle clogging during casting. The results herein show that the severe nozzle clogging of P‐containing high‐strength IF steel is related to the high MnO content in the slag and high P content in the liquid steel.